Outcomes of Neonatal Resuscitation Practices in Tertiary Care Hospital - Tufail Ahmed Soomro, Muhammad Zaki, Rizwana Qureshi, Bela Bashir, Asif Javeed, Neha Ahuja, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: neonatal birth asphyxia is a major cause of neonatal death and severe complications. It is associated with gestational complications as well as criticalities during delivery. Objective: To determine the outcomes of neonatal resuscitation practices in tertiary care hospital Study Design: Observational cross-sectional study Place and Duration of Study: Department of Paediatric, Ghulam Muhammad Mahar Medical College, Sukkur from 1st March 2023 to 31st August 2023. Methodology: One thousand two hundred and fifty deliveries were enrolled. Out of the total observed neonatal population, 138 newborns were identified with birth asphyxia. The neonatal resuscitation was performed by positive pressure ventilation (PPV) (20-30 seconds) by using a bag-valve-mask. Supplemental oxygen was initiated with 21% oxygen. Chest Compressions (if heart rate remains <60 bpm) was observed as 3:1 ratio with PPV (90 compressions, 30 breaths per minute). The AGPAR scoring method was applied. The overall practice score was categorized using the Bloom’s cut-off point as 80-100% Good, 60-79.9% Moderate and 00–59.9% poor. A resuscitated newborn was evaluated through APGAR score at post 05 min, followed by 10 minutes. Result: The majority of the neonates born were <37 weeks of their gestational age with a mean of 34.9±3.0 weeks of age. 53.6% of the neonates’ birth weight was less than 2.5 kg, bringing their birth health status to a very critical state. It was well noted that 15.2% of the neonates born through cesarean were breached. The present study has elaborated the fact that 16.7% of the neonatal cases resuscitated timely recovered well, 23 (16.7%) while 47.1% of the neonates required oxygen therapy, and 29% went into intensive care. Conclusion: The neonatal outcomes are significantly dependent on resuscitation technique and health professional skills. Keywords: Resuscitation, Neonatal, Asphyxia, Ventilation